2010
DOI: 10.1007/s10267-010-0059-2
|View full text |Cite
|
Sign up to set email alerts
|

A new acidophilic fungus Teratosphaeria acidotherma (Capnodiales, Ascomycota) from a hot spring

Abstract: A novel acidophilic fungus was isolated by an acidic enrichment culture of microbial mats and biofilms collected at an extremely acidic and high temperature hot spring. In culture studies, this fungus was revealed to produce ascomycetous teleomorph structures. Molecular phylogenetic study and morphological observation showed this fungus is a new species of the genus Teratosphaeria (Capnodiales, Dothideomycetes) and is phylogenetically close to Acidomyces acidophilus and Bispora sp., which were previously repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…In nature, acidic environments occur mainly in soils, lakes, swamps and peat bogs, and most fungi isolated from these acidic habitats are acid‐tolerant (Gross and Robbins, ). So far, only Acidomyces acidophilus (Selbmann et al., ), Acidomyces acidothermus (Yamazaki et al., ; Hujslová et al., ) and Hortaea acidophila (Hölker et al., ) in Teratosphaeriaceae , Acidothrix acidophila in Amplistromataceae (Hujslová et al., , ) and Penicillium lignorum (Stolk, ) in Eurotiales have been regarded as strictly acidophilic fungi. More than 35 Penicillium and Talaromyces species have been reported to be acid‐tolerant (Gross and Robbins, ; Dhakar et al., ; Houbraken et al., ) with three of these species belonging to Penicillium section Lanata‐divaricata , namely P. janthinellum (Dhakar et al., ), P. ochrochloron and P. simplicissimum (Gross and Robbins, ).…”
Section: Introductionmentioning
confidence: 99%
“…In nature, acidic environments occur mainly in soils, lakes, swamps and peat bogs, and most fungi isolated from these acidic habitats are acid‐tolerant (Gross and Robbins, ). So far, only Acidomyces acidophilus (Selbmann et al., ), Acidomyces acidothermus (Yamazaki et al., ; Hujslová et al., ) and Hortaea acidophila (Hölker et al., ) in Teratosphaeriaceae , Acidothrix acidophila in Amplistromataceae (Hujslová et al., , ) and Penicillium lignorum (Stolk, ) in Eurotiales have been regarded as strictly acidophilic fungi. More than 35 Penicillium and Talaromyces species have been reported to be acid‐tolerant (Gross and Robbins, ; Dhakar et al., ; Houbraken et al., ) with three of these species belonging to Penicillium section Lanata‐divaricata , namely P. janthinellum (Dhakar et al., ), P. ochrochloron and P. simplicissimum (Gross and Robbins, ).…”
Section: Introductionmentioning
confidence: 99%
“…All the acidophilic fungi hitherto reported are invariably anamorphic species; Teratosphaeria acidotherma A. Yamaz., K. Toyama, & Nakagiri is an exception and is phylogenetically related to A. acidophilus, recently described as a new teleomorphic species from acidic hot spring in Japan (Yamazaki et al 2010). In general, extremozymes have attracted a great deal of interest due to their potential for practical applications.…”
Section: Fungi From Polluted Environments: a Rich Source For Bioexplomentioning
confidence: 99%
“…Based on the homology analysis with other species, including Teratosphaeriaceae and other families, such as the Capnodiales of Mycosphaerellaceae, Capnodiaceae, Davidiellaceae, and Dissoconiaceae (26,27,28,29), we found that the T9 strain was located on the branch of the family Teratosphaeriaceae and the genus Penidiella in the phylogenetic tree (Fig. 6).…”
Section: Discussionmentioning
confidence: 99%
“…Teratosphaeria acidotherma, which is in a sister clade of Penidiella (Fig. 6), is an acidophilic fungus that prefers to grow at pH 2.0 to 5.0 (27). As the T9 strain was isolated from a low-moisture sample at an abandoned mine and grows better at pH 2.0 to 3.0, the strain has the typical characteristics of Teratosphaeriaceae.…”
Section: Discussionmentioning
confidence: 99%